Anisotropic photoluminescence of nonpolar ZnO epilayers and ZnO/Zn1 −xMgxO multiple quantum wells grown on LiGaO2 substrate - Yan, Tao; Trinkler, Laima E.; Korsaks, Valdis; Lu, Cheng Ying James; Berziņa, Baiba; Chang, Liuwen; Chou, Mitch Ming Chi; Ploog, K. H. (OSA - The Optical Society, 2020)
The temperature-dependent polarized photoluminescence spectra of nonpolar ZnO samples were investigated by 263 nm laser. The degree of polarization (DOP) of m-plane quantum wells changes from 76% at 10 K to 40% at 300 K, which is much higher than that of epilayer. The strong anisotropy was presumably attributed to the enhanced confinement effect of a one-dimension confinement structure formed by the intersection of quantum well and basal stacking fault. The polarization of laser beam also has an influence on the DOP. It is assumed that the luminescence polarization should be affected not only by the in-plane strains but also the microstructural defects, which do modify the electronic band structure.
Ministry of Science and Technology, Taiwan (104-2221-E-110-012-MY3, 107-2221-E-110-004-MY3); National Natural Science Foundation of China (51602309, U1605245).
Keywords: Research Subject Categories::NATURAL SCIENCES:Physics